Computational Intelligence Techniques in Health Care - Lakshmi, P.V.; Zhou, Wengang; Satheesh, P.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
This book presents research on emerging computational intelligence techniques and tools, with a particular focus on new trends and applications in health care. Healthcare is a multi-faceted domain, which incorporates advanced decision-making, remote monitoring, healthcare logistics, operational excellence and modern information systems. In recent years, the use of computational intelligence methods to address the scale and the complexity of the problems in healthcare has been investigated. This book discusses various computational intelligence methods that are implemented in applications in different areas of healthcare. It includes contributions by practitioners, technology developers and solution providers.
Bioinformatics, genomics and diabetes -- Coralyne targets proteases involved cancer progression: An InSilico study -- Computational Intelligence Approach for Prediction Of Breast Cancer Using Particle Swarm Optimization: A Comparative Study Of The Results With Reduced Set Of Attributes -- QSAR and validation analysis on MMP-13 Inhibitors -- Detection of Lesion in Mammogram Images using Differential Evolution based Automatic Fuzzy Clustering -- Sequence Alignment By Advanced Differential Evolutionary Algorithm (ADE) -- Swarm Intelligence and Variable Precision Rough Set Model: A Hybrid Approach for Classification -- Ayush To Kidney (Atok) Data Science Model for Diagnosis and to Advice Through an Expert System.
Keywords: Computational intelligence; Medical informatics; Biomedical engineering; Bioinformatics; Computational Intelligence; Health Informatics; Biomedical Engineering and Bioengineering; Computational and Systems Biology